Cyclometalated Iridium(III) Complexes as Two‐Photon Phosphorescent Probes for Specific Mitochondrial Dynamics Tracking in Living Cells. Issue 34 (21st July 2015) - Jin, Chengzhi; Liu, Jiangping; Chen, Yu; Zeng, Leli; Guan, Ruilin; Ouyang, Cheng; Ji, Liangnian; Chao, Hui
Abstract Five cyclometalated iridium(III) complexes with 2‐phenylimidazo[4, 5‐f][1, 10]phenanthroline derivatives (IrL1–IrL5) were synthesized and developed to image and track mitochondria in living cells under two‐photon (750 nm) excitation, with two‐photon absorption cross‐sections of 48.8–65.5 GM at 750 nm. Confocal microscopy and inductive coupled plasma‐mass spectrometry (ICP‐MS) demonstrated that these complexes selectively accumulate in mitochondria within 5 min, without needing additional reagents for membrane permeabilization, or replacement of the culture medium. In addition, photobleaching experiments and luminescence measurements confirmed the photostability of these complexes under continuous laser irradiation and physiological pH resistance. Moreover, results using 3D multicellular spheroids demonstrate the proficiency of these two‐photon luminescent complexes in deep penetration imaging. Two‐photon excitation using such novel complexes of iridium(III) for exclusive visualization of mitochondria in living cells may substantially enhance practical applications of bioimaging and tracking.